(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
This article aims to describe the structured control system based on the use of WhatsApp in Brazil, locating the relationships between influence strategies of the public debate carried out by national agents and the data market and algorithmic modulation strategies of Meta Plataforms Inc., company of technology that owns the platform. Starting from the concept of plataformization and an analytical approach influenced by the Actor-Network Theory, the WhatsApp is positioned in the analysis as a non-human sociotechnical member of a relationships network that involves economic and political objectives of human actors, leveling both in importance and understanding that the insertion of the platform profoundly changes the practices and forms of social organization in the country. The goal is to understand the conjectural conditions that make WhatsApp an important element in the lives of brazilian people and what is the Meta’s market model role for the control techniques that emerge with this use.